2021
DOI: 10.1021/acsnano.1c08038
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Effects on the Surfactant Adsorption and Interface Charging in Hexadecane/Water Emulsions

Abstract: Nanoscale properties at interfaces play a key role in the colloidal stability of emulsions and other soft matter materials where physical properties need to be controlled from the nano to macroscopically visible length scales. Our molecular level understanding of oil− water interfaces arises mostly from results at extended interfaces and the common view that emulsions are stabilized by a large number of surfactant molecules at the droplet's interface which, however, has been recently challenged. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…The fact that the addition of a substantial number of AuNPs to the water-oil interface did not generate any obvious changes to the size and morphology of the emulsions also suggested that there was already sufficient room at the water-oil interface of the CNT-stabilized emulsions to accommodate the additional AuNPs. This assembly model is consistent with previous reports which showed that only a sub-monolayer coverage of the particulate stabilizers is required to form stable Pickering emulsions 39,40 . In contrast, the stability of the Pickering emulsions was found to be less sensitive to the change in the concentration of CNT stabilizers.…”
Section: Synthesis Of Modifier-free Plasmonic Emulsionssupporting
confidence: 92%
“…The fact that the addition of a substantial number of AuNPs to the water-oil interface did not generate any obvious changes to the size and morphology of the emulsions also suggested that there was already sufficient room at the water-oil interface of the CNT-stabilized emulsions to accommodate the additional AuNPs. This assembly model is consistent with previous reports which showed that only a sub-monolayer coverage of the particulate stabilizers is required to form stable Pickering emulsions 39,40 . In contrast, the stability of the Pickering emulsions was found to be less sensitive to the change in the concentration of CNT stabilizers.…”
Section: Synthesis Of Modifier-free Plasmonic Emulsionssupporting
confidence: 92%
“…The charge density for the medium bleached hair surface is very similar to that measured for an SDS monolayer at the hexadecane–water interface (−37.9 μC cm −2 ). 84…”
Section: Methodsmentioning
confidence: 99%
“…The charge density for the medium bleached hair surface is very similar to that measured for an SDS monolayer at the hexadecane-water interface (À37.9 mC cm À2 ). 84 We also determined the root-mean-square (RMS) roughness of our model surfaces by obtaining a discrete time-averaged topography map of the surface. The surface was discretized by treating the coarse-grained beads as hemispheres with a radius equivalent to half the Lennard-Jones potential energy minimum s/2 and using a grid spacing of Dx = 0.071 nm À1 .…”
Section: Surface Propertiesmentioning
confidence: 99%
“…We notice that the halogen group of halonitrobenzenes and haloanilines is less polar while the nitro or amino group is polar, which makes it possible for both molecules to orient at oil−water interfaces. 49,50 With such a preferential molecular orientation, oil−water interfaces may regulate molecular adsorption patterns on the surfaces of metal NPs located in the inner interfacial layer. Thereupon, selective hydrogenation of p-chloronitrobenzene (p-CNB) was selected as a model reaction to investigate the impact of oil−water interfaces on the catalytic performances of metal NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%